Sequence Analysis of the 16SrRNA-rps12 Inverted Repeat Region in Chloroplast DNA of a Dendrobium Orchid - Benjawan Lertwiriyawong; Kisana Phinija; Pattana Srifah Huehne (Agriculture and Natural Resources, 2011)
The 16S ribosomal RNA (16SrRNA)-ribosomal protein S12 (rps12) DNA located in the inverted repeat regions (IRs) of chloroplast DNA (cpDNA) can be used as an efficient targeting region for plastid vector construction in plastid transformation systems. Thus, the 16S rRNA-rps12 cpDNA sequence of Dendrobium Jacquelyn Thomas ‘UH44-50’ was cloned and analyzed. The 3,782 base pair (bp) 16SrRNArps12 DNA sequence isolated from this Dendrobium cultivar was 97% similar to the related Phalaenopsis aphrodites (AY916449) and Oncidium Gower Ramsey (GQ324949) cpDNA. It was composed of the highly conserved sequence of 1,427 bp 16SrRNA at the 5′-end, 99 bp of rps12 at the 3′-end and 72 bp of the transfer RNA Valine (GAC) (trnV (GAC)). Nevertheless, the most variable regions were located in a 1,955 bp long spacer between the 3′-end trnV (GAC) and the 5′-end rps12. Apart from Phalaenopsis and Oncidium cpDNAs, the 16SrRNA-rps12 alignment of the Dendrobium nucleotide with nine other published sequences showed that this cpDNA region was unpredictably more homologous to Phoenix dactylifera, Liriodendron tulipifera and Drimys granadensis cpDNAs than those of grasses, including Oryza japonica, Triticum aestivum and Zea mays. The conserved and variable regions in the 16SrRNArps12 fragments of all twelve different species were located exactly in the same positions and orientation. Therefore, the highly conserved flanking regions of 16S rRNA-rps12 Dendrobium cpDNA have potential to be an appropriate homologous sequence for plastid transformation in orchids.